Intracranial solitary fibrous tumor/hemangiopericytoma: Report of two cases and literature review - Aljohani, Hani Talal; Chaussemy, D.; Proust, F.; Chibbaro, S. (International Journal of Health Sciences, 2017)
Intracranial solitary fibrous tumors (ISFTs) are rare mesenchymal neoplasms originating in the meninges and constitute a heterogeneous group of rare spindle cell tumors that include benign and malignant neoplasms of which hemangiopericytoma is nowadays considered a cellular phenotypic variant. ISFT usually shows benign or indolent clinical behavior. We describe two cases of ISFT managed in our institution along with a review of pertinent literature.